Rehabilitasi Melalui Ayat: Metode Qurani sebagai Jalan Transformasi Diri Narapidana - Fathoni, Achmad Robbi (Journal of Correctional Management, 2025)
This study aims to explore the impact of the Qurani method in teaching the Qur'an within correctional facilities, focusing on its effect on improving recitation skills and fostering religious character among inmates. The Qurani method, which employs a systematic and structured approach, helps participants gradually develop proficiency in reading the Qur'an. It consists of four stages: the introduction to Arabic letters, learning correct pronunciation with vowel marks, understanding tajwid rules, and practicing Qur'anic recitation with correct intonation. The method not only enhances technical skills in reading but also promotes spiritual and moral development, which are crucial for the rehabilitation of inmates. Despite its proven effectiveness, the implementation of this method faces challenges such as limited human resources, time constraints, and the varying motivation of inmates. Nevertheless, the Qurani method remains a promising tool for reintegrating inmates into society by improving their reading skills and instilling moral values.